Strategi Komunikasi Dakwah Syaikh Khanova Maulana dalam Pembinaan Al-Qur'an di Indonesian Al-Qur'an Center - Dede Faisal faisal; Malki Ahmad Nasir; Nia Kurniati (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. The strategy of Da’wah Communication of syaikh khanova maulana in the development of the Qur'an at the institution of Indonesian al-Qur’an Center This study aims to find out how the strategy of da’wah communication of Shaykh Khanova Maulana in developing the Al-Qur'an at the institution of Indonesian Al-Qur'an Center. In the process of preaching, the strategy of communicating is something very urgent that determines the success of his da'wah. As it is known that Shaykh Khanova Maulana is one of the people who has the highest Quranic sanad (transmission) in Indonesia. Later, with his communication strategy, he founded the Indonesian Al-Qur'an Center to increase the understanding of Al-Qur'an scholarship for the society, especially for teachers. This study aims to describe the role of Shaykh Khanova Maulana especially his da'wah strategy at the Institution. This type of research is qualitative with a descriptive approach, while the data collection techniques and the interview results are taken from observations which are supported by the documentation and library data. Abstrak. Penelitian ini bertujuan untuk mengetahui bagaimana strategi komunikasi dakwah Syaikh Khanova Maulana dalam pembinaan Al-Qur’an di lembaga Indonesian Al-Qur’an Center. Dalam proses berdakwah, strategi dalam berkomunikasi adalah suatu hal urgent yang menentukan terhadap keberhasilan dakwahnya. Syaikh Khanova Maulana adalah salah seorang yang memiliki sanad Al-Qur’an tertinggi di Indonesia. Dengan strategi komunikasinya ia mendirikan lembaga Indonesian Al-Qur’an Center untuk meningkatkan pemahaman terhadap keilmuan Al-Qur’an bagi masyarakat, terkhusus bagi para pengajar Al-Qur’an dan menjadi pelopor dalam hal pembinaan Al-Qur’an. Penelitian ini bertujuan untuk menggambarkan peran dan peranan srtategi dakwah Syaikh Khanova Maulana di lembaga Indonesian Al-Qur’an Center. Jenis penelitian tersebut bersifat kualitatif dengan pendekatan deskriptif, adapaun teknik pengumpulan data dan hasil wawanacara diambil dari observasi dan pengamatan yang didukung oleh data dokumentasi dan kepustakaan.